Effect of Gracilaria vermiculophylla Macroalga on Non-Alcoholic Fatty Liver Disease in Obese Rats - Maitane González-Arceo; Leixuri Aguirre; María Teresa Macarulla; Clàudia Gil-Pitarch; María Luz Martínez-Chantar; María P. Portillo; Saioa Gómez-Zorita (Antioxidants, 2024)
Marine algae are valuable sources of bioactive compounds that have the potential to be used in the management of various pathologies. Despite the increasing prevalence of NAFLD, the absence of an approved effective pharmacological treatment with demonstrable effectiveness persists. In this context, the aim of the present study is to assess the effect of Gracilaria vermiculophylla red seaweed dietary supplementation on hepatic lipid accumulation, as well as on oxidative stress, inflammation and fibrosis- related markers on obese fa/fa Zucker rats fed with a standard diet, supplemented or not with 2.5% or 5% dehydrated Gracilaria vermiculophylla. After a six-week supplementation with the macroalga, no significant reduction in hepatic total lipid content or hepatic triglyceride content was observed. However, both doses were able to diminish hepatic NEFA concentration by reducing de novo lipogenesis and increasing mitochondrial biogenesis. Moreover, supplementation with the dose of 2.5% improved some oxidative stress and inflammation-related markers. Supplementation with the dose of 5% did not exert these clear beneficial effects. Thus, this study demonstrates that while Gracilaria vermiculophylla may not mitigate hepatic steatosis, it could exert protective effects on the liver by reducing NEFA content and enhancing oxidative stress and inflammation parameters.